ENHANCING LANGUAGE LEARNING ATTITUDES THROUGH GAMIFIED LANGUAGE CAMPS: A 21ST CENTURY APPROACH - Mee, Rita Wong Mee; Pek, Lim Seong; Abd Rauf, Muhammad Fairuz; Amran, Mohd Fahmi Mohamad; Che Yob, Fatin Syamilah (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
Teachers are accustomed to traditional teaching, in which chalk-and-talk becomes the prominent approach in language teaching. Hence, planning a creative learning environment can be demanding as it comes with challenging tasks. However, the traditional way of teaching and learning can be inadequate for learners to retrieve knowledge in the 21st century classroom, as they prefer game-like activities rather than pen-and-paper lessons. Therefore, learners’ experience of using gamification in the classroom is significant as it sparks curiosity and immediate enthusiasm, which reflect the learners’ willingness to learn. Importantly, gamification prepares learners to be active and take responsibility for their learning. Fun games instilled during the lessons are believed to be more effective in producing positive outcomes due to learners feeling motivated to play more. However, learners would not realize that they are learning. This was followed by a selection of 108 respondents using gamification and a series of class activities in language learning at a local primary school in Kuala Selangor district, Selangor. The study was conducted using a quantitative survey method which involved administering questionnaires to the Language Camp participants at their respective schools. Data was collected, analyzed accordingly, and presented in the form of tables. The results showed that the integration of gamification in language learning aids learners to improve their creative, critical, and problem-solving skills. Likewise, interesting and engaging activities subconsciously spark the learners’ interest in language learning.